Frontal Sinus “Hump”: An Anatomical Risk Factor for Anterior Skull Base Injury in the Endoscopic Modified Lothrop Approach (Outside-In Frontal Drill-Out) - Teppei Takeda; Kazuhiro Omura; Haw Torng; Teru Ebihara; Satoshi Aoki; Kosuke Tochigi; Hiromi Kojima; Nobuyoshi Otori (Case Reports in Otolaryngology)
Skull base injuries caused by the outside-in frontal drill-out technique have not been reported. In this report, we chose an outside-in approach to open the frontal sinus for olfactory neuroblastoma resection. Although we identified the first olfactory fibre, the anterior skull base was damaged while drilling into the frontal sinus on the tumour side. We reconstructed the skull base in multiple layers using fascia and cartilage. Postoperative cerebrospinal fluid leakage or intracranial haemorrhage was not observed. In this case, a morphological difference existed in the posterior wall of the frontal sinus between the right and left sides, like a “hump” in the posterior wall of the frontal sinus. This case of damage to the anterior skull base that could not be avoided by identifying the first olfactory fibre alone is the first published case of skull base injury caused by the outside-in approach due to morphological variations of the frontal sinus and skull base. In this approach, the posterior wall of the frontal sinus cannot be observed because the intraoperative landmark is limited to the first olfactory fibre. Therefore, morphological variations of the posterior wall of the frontal sinus should be analysed in advance to prevent cranial base injury.